Role of additives in chiral amine-catalyzed direct aldol reaction - Sutar, R. L.; Joshi, Navalkishore N. (Synthetic Communications, 2014)
A systematic study of chiral adducts derived from amines as catalysts for aldol reaction revealed that enantioselective outcome depends on the chiral enamine intermediate and not the face-selective activation of aldehyde. A simple addition compound of proline and 8-hydroxy quinoline was found to be a good catalyst. [Supplementary materials are available for this article. Go to the publisher's online edition of Synthetic Communications (R) for the following free supplemental resource(s): Full experimental and spectral details.]
Keywords: Additives; Aldol reaction; chiral amines; organocatalyst; pyrrolidine-catalyzed